2016
DOI: 10.24198/jkg.v28i3.18695
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identifikasi usia berdasarkan metode Al Qahtani melalui radiograf panoramik di RSGM FKG UNPAD</p><p>Age identification based on Al Qahtani method through panoramic radiograph at the Dental Hospital of Universitas Padjadjaran</p>

Abstract: ABSTRAKPendahuluan: Perkiraan usia dilakukan untuk mengetahui usia seseorang. Saat ini perkiraan usia banyak digunakan, kepentingannya adalah untuk forensik dan bidang kedokteran gigi. Tujuan dari penelitian ini adalah mengetahui apakah Metode Al Qahtani mampu mengidentifikasi usia melalui radiograf panoramik di RSGM FKG Unpad. Metode: Penelitian ini dilakukan secara deskriptif sederhana dengan menggunakan software atlas Metode Al Qahtani, dengan melihat perkembangan gigi dan tingkat erupsi dari masing-masing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Apart from the Demirjian and Willems methods, the Al Qahtani method also has high accuracy and is the most modern method. This was proven by Rusydiana et al [ 29 ], who examined 94 samples. Of the 94 samples tested, 66 of them got a similar result to the patient's age.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Apart from the Demirjian and Willems methods, the Al Qahtani method also has high accuracy and is the most modern method. This was proven by Rusydiana et al [ 29 ], who examined 94 samples. Of the 94 samples tested, 66 of them got a similar result to the patient's age.…”
Section: Discussionmentioning
confidence: 80%
“…In the research by Rusydiana et al in 2016, a total of 94 samples were calculated using the Al Qahtani method. The results showed that 66 (70.21%) of the samples using the method were able to get a good result of estimating the patient's chronological age, while the rest of 28 (29.79%) of the samples' estimation results were significantly different from the patient's chronological age [ 29 ].…”
Section: Tooth Growth and Developmentmentioning
confidence: 99%